COMPARATIVE CHARACTERISTICS OF RESULTS PHYSICAL PREPARABILITY TEST POPULATION OF UKRAINE IN RUNNING 100 METERS ON AT THE BEGINNING AND AT THE END OF THE SCHOOL YEAR STUDENTS AND KEIKNEU COURSE IN 1999/2000 AND 2002/2003 ACADEMIC YEARS (Pedagogy of Higher and Secondary Education, 2004)
Attentive vision at the results of the state test on speed.